Covid-19 Vaccination in Nasopharyngeal Carcinoma Patients during COVID-19 Pandemic - Irnanda Warda Rizki Nasution; Farhat Farhat; Elvita Rahmi Daulay (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is one kind of cancer that is the most common type of head and neck malignancy, arising from the posterior and lateral parts of the nasopharynx especially from torus tubarius or pharyngeal recess or the other name is Rosenmüller fossa. This shows significant differences from other head and neck cancers, clinical behavior, cause, epidemiology, treatment, as well as prognosis. Clinical trials of COVID-19 vaccines with better follow-up will provide useful data on vaccine advantages in patients receiving cancer treatment, due to the absence of complete data to determine the relationship between active oncology treatment and the power to induce immunity to COVID-19 using the vaccine. Discussion: The primary aim of vaccines is to produce stimulation by the antigen we desire in the presence of sufficient infection to elicit memory immunity with tolerable protection.[15] Due to the increasing frailty of cancer patients with infection as well as deaths from COVID-19, there is an urgent need to vaccinate patients with COVID-19 cancer. Various considerations for the protection and benefits that are expected to have an effect with treatment due to their standart management and changes in the immune system of patients with malignancies. Conclusion The COVID-19 vaccine, granted approved or permitted, will be considered the basic of prevention of this COVID-19 pandemic for patients with nasopharyngeal carcinoma. There are advantages and disadvantages about Covid-19 vaccine. Then, a quality direction on clinical trials of patients with cancer and COVID-19 vaccines becomes very attractive. Finally, comprehensive oncological care requires cancer patients to be prioritized for the COVID-19 vaccine